B-type natriuretic peptide, disease progression and clinical outcomes in atrial fibrillation. Issue 5 (18th September 2018) - Inohara, Taku; Kim, Sunghee; Pieper, Karen; Blanco, Rosalia G; Allen, Larry A; Fonarow, Gregg C; Gersh, Bernard J; Ezekowitz, Michael D; Kowey, Peter R; Reiffel, James A; Naccarelli, Gerald V; Chan, Paul S; et al.
Abstract : Objective: The association with B-type natriuretic peptide (BNP), disease progression and outcomes in patients with atrial fibrillation (AF) has not been thoroughly investigated. Methods: We evaluated the association between BNP levels and outcomes, including AF progression, composite outcome of major adverse cardiovascular or neurological events (MACNE) and major bleeding, via pooled logistic regression and Cox frailty models in Outcomes Registry for Better Informed Treatment of Atrial Fibrillation II registry. AF progression was defined as either paroxysmal becoming persistent or permanent, or persistent becoming permanent at any follow-up. Results: Among 13 375 patients with AF, 2797 with BNP values at baseline (median age (IQR), 72.0 (63.0–80.0) years; 43.0% women; median BNP, 238 (102–502) ng/L; 42.3% prior heart failure) were included in the models evaluating the association between BNP levels and MACNE or major bleeding. Of these, 1282 patients with paroxysmal or persistent AF at baseline were analysed in AF progression model. The likelihood of AF progression (adjusted OR, 1.11 for every 100 ng/mL; 95% CI 1.03 to 1.19) and MACNE (adjusted HR, 1.11 for every doubling in BNP values; 95% CI 1.01 to 1.22) increased with BNP concentration, while the elevated BNP values were not associated with increased risks of major bleeding. BNP values improved the risk prediction of AF progression and MACNE when added to conventional risk estimates. Conclusions: BNP levels are associated with increased risk of AF progression and cardiovascular outcomes in patients with AF. Further studies are required to assess whether biomarker-based risk stratification improves patient outcomes. Clinical trial registration: NCT01701817 .